Fundamentals of Entrepreneurship (ENT 300) : Galaxy Cybercafe / Thomas Baos … [et al.] - Baos, Thomas; Lanchang, Kereen Samban; Sulainan, Sheril Nur Haziani (2017)
Galaxy Cybercafe, unlike most cafes will provide a unique forum for communication and entertainment through the medium of the internet. Galaxy Cybercafe is the answer to an increasing demand. To provide to the general public to access to the methods if communication and volumes of information how available on the internet and to access at a cost they can afford and in such a way that they are not socially, economically, or politically isolated. Galaxy Cybercafe's goal is to provide the community with a social, educational, entertaining, atmosphere for worldwide communication.